2016
DOI: 10.1002/jemt.22629
|View full text |Cite
|
Sign up to set email alerts
|

Involution dependent changes in distribution and localization of bax, survivin, caspase‐3, and calpain‐1 in the rat endometrium

Abstract: The endometrial layer of the uterus is characterized by continuous cycle of cell growth and apoptosis in response to hormonal changes. Apoptosis is regulated by several apoptotic regulators, but their significance in involuting uterus has not been well understood. For that reason, aim of this study was to investigate possible role of apoptosis-related proteins (bax and survivin) and enzymes (caspase-3 and calpain-1) in the involuting uterus of the rat, using immunohistochemistry. Our results indicated cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…This result suggested that the miR‐26a increase the p53 protein levels in the EECs but decreased in ESCs of dairy goats. A key caspase involved in apoptosis was Caspase‐3 (also called CPP32, Yama, or apopain), which was activated during the early stages of apoptosis (Alan & Liman, ). Because Caspase‐3 was the main executioner of apoptosis, the active form of Caspase‐3 was one of the most used diagnostic tools for detecting apoptosis in many cell types (Gown & Willingham, ; Jin & El‐Deiry, ).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggested that the miR‐26a increase the p53 protein levels in the EECs but decreased in ESCs of dairy goats. A key caspase involved in apoptosis was Caspase‐3 (also called CPP32, Yama, or apopain), which was activated during the early stages of apoptosis (Alan & Liman, ). Because Caspase‐3 was the main executioner of apoptosis, the active form of Caspase‐3 was one of the most used diagnostic tools for detecting apoptosis in many cell types (Gown & Willingham, ; Jin & El‐Deiry, ).…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 (also termed CPP32, or apopain) is activated during the early stages of apoptosis [110] and it is the primary executioner of apoptosis, so the expression levels of Caspase-3 is one of the most common used detect indicator to evaluate the apoptosis of many cell types in previous studies [111, 112]. Furthermore, several studies have suggested that endometrial cell death is regulated by Caspase-3 during the menstrual or estrous cycle [113] and during early pregnancy [114].…”
Section: Discussionmentioning
confidence: 99%